PENGUATAN IDENTITAS SOSIAL MASYARAKAT MINORITAS ETNIS INDIA TAMIL DI KAMPUNG KELING KOTA TEBING TINGGI - Devano Barus, Muhammad Nanda; Ritonga, Sakti; Ismail, Ismail (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
The aim of the research is to find out what strategies to strengthen social identity are carried out by the Tamil Indian ethnic minority community in Kampung Keling, Tebing Tinggi City. The strengthening of identity in question is due to the identity crisis experienced by the Tamil community from various aspects which then gives rise to a feeling of maintaining existence as an ethnic group. This research uses qualitative methods with a descriptive approach. The theory used in this research is Henri Tajfel's Social Identity Theory. The results of this research are that the Tamil community in Kampung Keling is experiencing an identity crisis related to the use of the Tamil language. Tamil is only mastered by older people and only some teenagers can speak Tamil, while for children, almost all of them cannot master Tamil. Then there are efforts being made to strengthen the identity of the Tamil community, namely by the way parents teach their children how to speak Tamil, then there are plans to build a Tamil Hindu school to make it easier for children to learn about Tamil religion and culture. Another effort is the use of traditional clothing during worship or holding celebrations related to Tamil Indian traditions such as the Adhi Maha Puja tradition which is usually held once every year.